Gambaran hasil laboratorium pasien COVID-19 di RSUD Bali Mandara: sebuah studi pendahuluan - I Gusti Ayu Mardewi; Nyoman Trisna Yustiani (DiscoverSys Inc., 2021)
Background: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is an infection with CoronaVirus Disease-2019 (COVID-19) which has an impact on laboratory results parameters. Laboratory values that do not play an important role to help classify and assess the prognosis of patients so that it can provide earlier therapy which is expected to achieve a better outcome. This preliminary research aims to see the description of the laboratory results of COVID-19 patients at Bali Mandara Hospital.Methods: This type of research is descriptive research. The number of samples in this study were 76 samples obtained by the total sampling technique. Data obtained from secondary data, namely sample medical records. Laboratory parameters that conquered this study include complete blood count, D-Dimer, Neutrophil Lymphocyte Ratio (NLR), to C-Reactive Protein (CRP). Data were analyzed using SPSS version 17 for Windows.Results: The mean age of the patients was 50.86±13.9 years-old, with the dominant female being (53.9%). Most of the patients treated in non-ICU rooms with a mean treatment duration of 18.86±11.5 days. Laboratory results showed that the NLR value was> 3.13 in 50% of patients, 13.3% had an increase in Procalcitonin (PCT), 63.2% of patients had an increase in CRP, and as many as 76.3% of patients had a D-Dimer value < 2 µg/mL. For the levels of lymphocytes, platelets, and hemoglobin, most of the patients had normal values.Conclusion: This study provides epidemiological profile data and laboratory parameter profiles of COVID19 patients. Variations in various laboratory result parameters require more in-depth research to see predictors that significantly affect mortality and morbidity of COVID19 patients during treatment. Latar Belakang: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) adalah suatu infeksi penyebab penyakit CoronaVirus Disease-2019 (COVID-19) dimana memiliki dampak pada hasil parameter laboratorium. Nilai laboratorium yang tidak normal berperan penting untuk membantu mengelompokkan dan menilai prognosis pasien sehingga dapat memberikan terapi lebih awal yang diharapkan dapat mencapai luaran yang lebih baik. Penelitian pendahuluan ini bertujuan untuk mengetahui gambaran hasil laboratorium pasien COVID-19 di RSUD Bali Mandara.Metode: Jenis penelitian yang dilakukan yaitu penelitian deskriptif. Jumlah sampel pada penelitian ini adalah 76 sampel yang didapat dengan teknik Total Sampling. Data diperoleh dari data sekunder yaitu rekam medis sampel. Parameter laboratorium yang dinilai pada penelitian ini meliputi pemeriksaan darah lengkap, D-Dimer, Neutrophil to Lymphocyte Ratio (NLR), hingga C-Reactive Protein (CRP). Data dianalisis dengan SPSS versi 17 untuk Windows.Hasil: Rata-rata usia pasien yaitu 50,86±13,9 tahun dengan dominan perempuan (53,9%). Sebagian besar pasien dirawat di ruang non-ICU dengan rata-rata durasi perawatan 18,86±11,5 hari. Hasil laboratorium didapatkan nilai NLR >3,13 pada 50% pasien, 13,3 % peningkatan Procalcitonin (PCT), 63,2% pasien mengalami peningkatan CRP, dan sebanyak 76,3% pasien memiliki nilai D-Dimer < 2 µg/mL. Untuk kadar limfosit, trombosit, maupun hemoglobin sebagian besar pasien memiliki nilai yang normal.Kesimpulan: Pada penelitian ini memberikan data profil epidemiologi dan profil parameter laboratorium pasien COVID19. Variasi hasil parameter laboratorium yang beragam memerlukan penelitian lanjutan yang lebih mendalam untuk mengetahui prediktor yang signifikan mempengaruhi mortalitas dan morbiditas pasien COVID19 selama perawatan.